Microtensile Bond Strength of Etch-and-Rinse Adhesives in Different Hydroabrasion Conditionings - Michele Tepedino; Maciej Iancu Potrubacz; Antonella Imperiale; Claudio Chimenti; Mario Capogreco; Maurizio D'Amario (Hindawi Limited, 2021)
The aim of the present study was to in vitro evaluate the effect of dentin conditioning with hydroabrasion on the microtensile bond strengths of three adhesive systems, compared to the standard etch-and-rinse technique. Sixty extracted human third molars were collected, and their midcoronal occlusal dentin was used for the microtensile bond strength test. Teeth were randomly assigned to three groups according to the adhesive system used: ExciTE F DSC, ENA Bond, and Scotchbond Universal. Specimens from each group were further divided into four subgroups: control specimens were treated with standard adhesive procedures; hydroabraded (HA) specimens were subjected to preventive hydroabrasion with three different intensity levels. After bonding procedures, composite crowns were incrementally built up. After thermocycling, specimens were subsequently sectioned into 1 × 1 mm sticks, and microtensile bond strengths were measured. Data were statistically analyzed. Failure mode analysis was performed. There were no significant differences in terms of bond strength between standard adhesion protocols and adhesion with HA preconditionings. On the other hand, the type of adhesive used had a significant effect on the tensile bond strength. Subgroups treated with hydroabrasion at higher intensity showed a slightly increased frequency of cohesive fractures. In conclusion, hydroabrasion can be used for dentin cavity preparation or finishing, since it does not seem to affect the bonding effectiveness.